SYNTHESIS AND CHARACTERIZATION OF ALUMINIUM-BARIUM NITRATE MATRIX COMPOSITES - Pillai, Lakshmanan; G.R, Jinu.; R, Elansezhian. (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
In this experimental study the Aluminum based Metal Matrix Composites were synthesized by means of melt stir casting set up in an economic manner without sacrificing the potential properties of constituent materials. The industries are focusing their interest in composites containing light weight, low density with high strength and low cost reinforcements. .In this investigation, commercially available Aluminum 6063 T1 alloy is taken as matrix and special choice of a chemical agent barium nitrate as reinforcement material to fabricate the composites. Barium is a high chemical reactivity element with symbol Ba and atomic number 56.The present investigation has been focused on the utilization of dispersing particles of 2%,4%,6%,8% and 10% of wt into aluminum 6061 to produce composites by stir casting method to prepare the specimens. The wear and hardness characteristics of aluminum with barium nitrate composites are assessed with a computerized pin-on-disc machine and Rockwell hardness tester. The mechanical parameters such as ultimate tensile strength, elongation and breaking point are evaluated and found that increases with increase in addition of reinforcement up to 6% of weight and then slightly reduces. The Hardness values of the composition of Aluminum metal matrix increases from 61 RHN to 86 RHN due to incorporation of particles. The wear rate trend starts decreasing with increase in weight percentage of Ba(No3)2 in the matrix. The impact strength of the metal matrix composites increases with increase in addition of the reinforcement material. The maximum impact strength is 5.69 J is obtained at weight percentage of 10% of barium nitrate.